Does side matter? Deciphering mechanisms that underpin side-dependent pathogenesis and therapy response in colorectal cancer - Harrison J. Boka; Rebekah M. Engel; Christine Georges; Paul J. McMurrick; Helen E. Abud (Molecular Cancer)
Abstract Colorectal cancer (CRC) is stratified by heterogeneity between disease sites, with proximal right-sided CRC (RCRC) multifactorial in its distinction from distal left-sided CRC (LCRC). Notably, right-sided tumors are associated with aggressive disease characteristics which culminate in poor clinical outcomes for these patients. While factors such as mutational profile and patterns of metastasis have been suggested to contribute to differences in therapy response, the exact mechanisms through which RCRC resists effective treatment have yet to be elucidated. In response, recent analyzes, including those utilizing whole genome sequencing, transcriptional profiling, and single-cell analyses, have demonstrated that key molecular differences exist between disease sites, with differentially expressed genes spanning a diverse range of cellular functions. Here, we review and contextualize the most recent data on molecular biomarkers found to exhibit discordance between RCRC and LCRC, and highlight candidates for further investigation, including those which present promise for future clinical application. Given the present disparity in survival outcomes for RCRC patients, we expect the prognostic biomarkers presented in our review to be useful in establishing future directions for the side-specific treatment of CRC.